2009
DOI: 10.1080/07357900802146204
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of Foxo3a is Associated with Poor Prognosis in Ovarian Cancer Patients

Abstract: To investigate whether Foxo3a expression is correlated with p27(kip1) protein levels as well as how it might be clinically relevant, we evaluated the expression of Foxo3a in several ovarian tumors. Immunohistochemical analysis was performed in 63 cases of ovarian tumors. Ten cases were evaluated by Western blot analysis. There was a correlation observed between Foxo3a over-expression and clinic pathological parameters (p = 0.032). Kaplan-Meier survival analysis showed that Foxo3a low expression was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 37 publications
3
59
0
Order By: Relevance
“…FOXO3 acts as a suppressor of follicular activation at the earliest stages of follicular growth in mice (26). Low expression of FOXO3 has been significantly associated with poor prognosis in ovarian cancer patients (27). Detainment of FOXO3 could therefore be one option to treat ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FOXO3 acts as a suppressor of follicular activation at the earliest stages of follicular growth in mice (26). Low expression of FOXO3 has been significantly associated with poor prognosis in ovarian cancer patients (27). Detainment of FOXO3 could therefore be one option to treat ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that low expression of FoxO3a in ovarian cancer is associated with poor prognosis of patients (Fei et al, 2009). Higher CCNG2 expression also correlates with recurrence-free survival in breast cancer patients (Adorno et al, 2009).…”
Section: Nodal Induces Cyclin G2 Transcription Via Foxo3a G Fu and C mentioning
confidence: 98%
“…In the future, it would be interesting to explore the potential relationship between genetic variation in FOXO3A and various cancers from the viewpoint that the former is a potential tumor suppressor (Fei et al 2009;Hu et al 2004;Mikse et al 2010;Yang et al 2008). So far, little is known about the link between germ line FOXO3A variation and a predisposition to cancer (Campa et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It also plays an important role in growth arrest, DNA repair, and apoptosis in response to DNA damage and oxidative stress (Furukawa-Hibi et al 2002;Greer and Brunet 2005;Kops et al 2002;Tran et al 2002). Furthermore, FOXO3A has been implicated as a tumor suppressor (Fei et al 2009;Hu et al 2004;Mikse et al 2010;Yang et al 2008), and FOXO3A activity was consistently found to be downregulated in various cancers (Yang and Hung 2009;Greer and Brunet 2005). More recently, FOXO3A was also reported to stimulate a proapoptotic transcriptional program in response to a human lung carcinogen , and the FOXO3A gene region is a target of somatic deletion in lung adenocarcinoma (LAC) in both humans ) and mice (Herzog et al 2009).…”
Section: Introductionmentioning
confidence: 99%